Oncogenic BRAF mutations and p16 expression in melanocytic nevi and melanoma in the Polish population - Mackiewicz-Wysocka, Małgorzata; Czerwińska, Patrycja; Filas, Violetta; Bogajewska, Elżbieta; Kubicka, Agata; Przybyła, Anna; Dondajewska, Ewelina; Kolenda, Tomasz; Marszałek, Andrzej; Mackiewicz, Andrzej (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2017)
Introduction: Twenty-five – fifty percent of skin melanomas arise from nevi. Melanocyte proliferation is activated by BRAF V600E , then is arrested, but single nevi transform to melanomas. p16 controls arrest, and p16 loss may promote transformation. Aim : To analyze BRAF V600E , p16 expression and melanocyte proliferation in dermal, compound and dysplastic nevi, cells of primary and metastatic melanoma in the Polish population. Material and methods : One hundred and thirty-two nevi (dermal, compound, dysplastic) and 41 melanomas (in situ, primary, metastatic) were studied. BRAF was assessed by cobas® 4800 BRAFV600 Mutation Test, High Resolution Melting Assay validated with: pyrosequencing and immunohistochemistry. p16 and Ki67 expression was analyzed by IHC. Results : Eighty-two percent of nevi and 57% of melanomas display BRAF V600E expression. Most dermal and compound nevi had > 50% of p16(+) cells. BRAF V600E dysplastic nevi had a low number of p16(+) cells. Nevi without BRAF V600E (WT), had 90% of cells p16(+). In 60% of in situ and primary melanomas, there was a low number of cells of p16(+). Fifty percent of WT metastatic melanoma and 33% of BRAF V600E showed a high level of p16. The number of Ki67(+) cells in dysplastic nevi was very low. In 25% of BRAF V600E melanomas in situ and 55% of WT, > 10% cells were Ki67(+). All BRAF V600E primary melanomas and 66% of WT had > 10% Ki67(+) cells. Twenty percent of BRAF V600E and WT metastases had > 10% of Ki67(+), however, 62% of BRAF V600E and 32% of WT samples had > 50% of Ki67(+) cells. Conclusions : BRAF V600E and p16 are more frequent in nevi than in melanoma in vivo. A significantly higher p16 expression was observed in mutated nevi than in WT, while in melanoma it was just the opposite. The proliferation rate of melanoma cells negatively correlated with p16 expression.